EFL STUDENT TEACHERS’ PRE-TEACHING PERFORMANCE - Rivi Antoni (JEE (Journal of English Education), 2016)
This article is concerned with the study of student teachers’ pre-teaching performance at class VI/A English department at university of Pasir Pengaraian in academic year 2014. The aspects explored in the study involved students’ activities in the learning of TEFL II course. The research employed the descriptive quantitative design. The instruments used in collecting the data were the performance test and classroom. The data analysis showed the presentation and analysis of data. The findings showed that the the student teacher’s pre-teaching performance were in the level of fair, especially on the performance of opening the lesson, comprehension of learning materials, teaching and learning activities and evaluation.